The Effect of Ambiguity Tolerance Therapy, on Uncertainty, Worry and Vitality of Mothers Suffering from Generalized Anxiety Disorder with Mentally Disabled Children - Fatemeh Movahedi; Shahnaz Khaleghipour (مطالعات روانشناختی, 2022)
The purpose of this study was, to determine the effect of ambiguity tolerance therapy on uncertainty, worry, and vitality of mothers suffering from generalized anxiety disorder having mentally disabled children in Isfahan. The method was semi-experimental, and in the form of pretest and posttest with the control group. By the purposive sampling method, 30 people who had the inclusion criteria for the research were selected and were randomly replaced into two experimental and control groups. The instruments were, Generalized Anxiety Disorder Questionnaire, the scale of Intolerableness of uncertainty, Pennsylvania Worry Questionnaire, and Mental Vitality Questionnaire. After performing the pretest, the experimental group underwent ambiguity tolerance therapy, in 12 sessions of 60 minutes. The results showed that ambiguity tolerance therapy was effective on intolerance of uncertainty, anxiety and also increasing the vitality of mothers with generalized anxiety disorder, who had children with disabilities. Therefore, this treatment method can be used to reduce intolerance uncertainty, anxiety and increase vitality.